Youth for Cooperative, Why Not? - Miya Dewi Suprihandari; Sri Lestari; Mochamad Ardi Setyawan (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
The younger generation is the next generation of the nation in all respects, so that the nation becomes better. They are obliged to protect what has become the basis of a nation from changes that can eliminate the characteristics of a nation. The ability of the next generation must be supported to develop by the nation and state, so that the characteristics of a nation and state can be maintained and developed for the better for the whole community, for example cooperatives. The development of the world makes most of the younger generation less remember and less interested in developing one of the characteristics of the nation in the economic field. So that at this time the existing cooperatives tend to appear underdeveloped in Indonesia, because there tends to be a lack of regeneration in their organizational structure. To overcome this, the government should also assist the process of making cooperatives into organizations that are able to attract the younger generation to work for the organization and community members who are part of it, and help the government seek to increase people's income, whether they are members or not.